Strategi Komunikasi Salam TV Dalam Menyiarkan Dakwah Islam Melalui Media - Andini Nur Bahri; Annisa Julianti Kudairi; Anggi Meruah Purba; Jarosim Simbolon; Novi lestari (Lembaga Pengembangan Kinerja Dosen, 2023)
The communication system is related to the growing communication network in society. The components discussed when discussing communication systems include non-media communication systems and media communication. This type of research is qualitative research which describes data using a series of sentences. The method used in this research is descriptive method. Descriptive method is a method whose data sources are words, pictures, and data from books, journals and other scientific works. In addition, everything that is collected is likely to be the key to what has been researched. So the use of this method does not produce data in the form of numbers, but data that is descriptive in nature. This study uses written data sourced from scientific journals and previous research. In today's digital era, da'wah media is very important in spreading religious messages, especially in Islam. Salam TV is a communication system that plays an important role in spreading Islamic da'wah through da'wah media. Through Salam TV, Islamic da'wah messages can reach a wide audience, convey the right da'wah messages, play a role in religious education, and encourage positive social interaction.